Comparision of Nerve Flossing and Conventional Therapy with Only Conventional Therapy for Sciatica - Darshana Chaudhary (International Journal of Allied Medical Sciences and Clinical Research, 2020)
Background Sciatica is one of the most common painful and disabling conditions affecting about 40% of low back pain cases and 1.6% - 43% of adult population annually. Many conventional physiotherapeutic modalities have been used to manage sciatica but the effect of Nerve Flossing Technique (NFT), which is a cost effective treatment option in the management of acute sciatica is yet to be investigated. Aim This study was therefore conducted to compression of nerve flossing and conventional therapy with only conventional therapy for sciatica. Methods A pretest-posttest control experimental design, involving 30 participants from DR. Ulhas patil college and hospital, with sciatica were randomly assigned into two groups; Group A (control group) received only Conventional Physiotherapy that is traction and TENS and group B (Experimental group ) received NFT in addition with Conventional Physiotherapy. The outcome of the study was assessed using visual analogue scale (VAS) and Straight Leg Raise (SLR). Results The result of this study revealed the experimental group had significant (P<0.01) improvement in both outcome measures when compared to the control group. Conclusion Nerve Flossing Technique reduced sciatica and improved hip range of motion hence can be utilized in the treatment of patient with sciatica.